The dollar and the German stock market: determination of exposure to and pricing of exchange rate risk using APT-modelling - Horst Entorf; Gösta Jamin (Technische Universität Darmstadt, Department of Law and Economics, 2003)
We estimate the impact of dollar changes on the value of German DAX corporations, using APT-modelling for the period 1977 - 1995. Several macroeconomic risk factors, including the dollar and a residual market factor representing the general market risk, are specified. The general notion is that the export-oriented German companies should benefit from increasing dollar values. We find time-varying dollar exposure presumably depending on the prevailing trade regime. Dollar sensitivity is positive as expected in periods with a positive trade balance, whereas it turns negative in periods with a negative trade balance (e.g., in the first half of the 1980s). APT-modelling simultaneously considers exchange rate exposure and risk-premia of macroeconomic risk factors, the latter also being unstable over time.
Keywords: F31; G12; 330; Börsenkurs; Währungsrisiko; US-Dollar; Arbitrage Pricing; Schätzung; Deutschland